Indications and Visual Outcomes of Corneal Transplant Surgery in Tanzania (Tanzania Medical Journal, 2025)
Background: Corneal diseases are among the major causes of visual impairment and blindness worldwide, after cataract and glaucoma. They account for approximately 7% of all blindness worldwide.  Corneal transplantation, an operation that replaces diseased corneal tissue with a healthy donor cornea, is increasingly in demand. Current information on corneal transplant indications, outcomes, and associated factors is crucial for planning corneal transplant services in resource-limited settings like Tanzania.Aim: To determine the indications, visual outcomes, and associated factors among patients who underwent corneal transplant at tertiary eye units in Tanzania.Methods: A hospital-based retrospective review and analysis of clinical records of all patients who underwent corneal transplant between January 2018 and September 2021 at Dr. Agarwals Eye Hospital and Kilimanjaro Christian Medical Centre. The data was extracted by a data collection tool from the case notes. Descriptive and logistic regression analyses were conducted using Statistical Package for Social Sciences version 23.Results: Out of 98 patients who had undergone corneal transplant at the two eye departments, 58% were males. The median recipient age was 22 (IQR 17, 38) years. Keratoconus was the most common indication 58 (54.7%), followed by central corneal scar 19 (17.9%), and bullous keratopathy 10(9.4%). Preoperatively, 77.4% of eyes were blind, and none had normal vision. Postoperatively, 44.3% achieved normal best corrected vision at 6 months post-transplant. Patients with keratoconus (aOR: 0.032, 95% CI: 0.058-0.945, p = 0.035) and participants aged ≤ 40 years (aOR: 0.019, 95% CI: 0.001-0.452, p=0.014) were less likely to have poor visual outcome while presence of postoperative complications (aOR: 3.632, 95% CI: 1.107-11.915, P = 0.033) and postoperative increased intraocular pressure (aOR: 1.193, 95% CI 0.294-0.848, p = 0.025) were associated with poor visual outcomes.Conclusion and recommendation: Keratoconus is the leading indication for corneal transplant. Vision improved significantly following corneal transplantation; however, postoperative complications and increased intraocular pressure were associated with poor visual outcomes. There is a need to establish more corneal transplant services, as they have shown satisfactory outcomes in our setting.